Tianeptine antagonizes the reduction of PV+ and GAD67 cells number in dorsal hippocampus of socially isolated rats - Peric, Ivana; Inta, Dragos; Gass, Peter (Progress in neuro-psychopharmacology & biological psychiatry, 2019)
Adult male rats exposed to chronic social isolation (CSIS) show depressive- and anxiety-like behaviors and reduce the numbers of parvalbumin-positive (PV+) interneurons in the dorsal hippocampus. We aimed to determine whether tianeptine (Tian), administered during the last three weeks of a six-week-social isolation (10mg/kg/day), may reverse CSIS-induced behavioral changes and antagonize the CSIS-induced reduction in the number of PV+ interneurons. We also studied whether Tian affects the GABA-producing enzyme GAD67+ cells, in Stratum Oriens (SO), Stratum Pyramidale (SP), Stratum Radiatum (SR) and Stratum Lacunosum Moleculare (LM) of CA1-3, as well as in molecular layer-granule cell layer (ML-GCL) and Hilus (H) of the dentate gyrus (DG). CSIS-induced reduction in the number of PV+ cells was layer/subregion-specific with the greatest decrease in SO of CA2. Reduction in the number of PV+ cells was significantly higher than GAD67+ cells, indicating that PV+ cells are the main target following CSIS. Tian reversed CSIS-induced behavior phenotype and antagonized the reduction in the number of PV+ and GAD67+ cells in all subregions. In controls, Tian led to an increase in the number of PV+ and GAD67+ cells in SP of all subregions and PV+ interneurons in ML-GCL of DG, while treatment during CSIS, compared to CSIS alone, resulted with an increase of PV+ interneurons in SO and SP CA1, SP CA2/CA3 and ML-GCL DG with simultaneous increase in GAD67+ cells in all CA1, LM CA2, SO/SR/LM CA3. Data show that Tian offers protection from CSIS via modulation of the dorsal hippocampal GABAergic system.